2005
DOI: 10.1177/1090198105275046
|View full text |Cite
|
Sign up to set email alerts
|

More Than a Message: Framing Public Health Advocacy to Change Corporate Practices

Abstract: Framing battles in public health illustrate the tension in our society between individual freedom and collective responsibility. This article describes how two frames, market justice and social justice, first articulated in a public health context by Dan Beauchamp, influence public dialogue on the health consequences of corporate practices. The authors argue that public health advocates must articulate the social justice values motivating the changes they seek in specific policy battles that will be debated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
171
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(173 citation statements)
references
References 11 publications
0
171
0
2
Order By: Relevance
“…Iyengar (18) has found that such episodic news results in audience interpretations that tend to blame the victim, whereas more thematic news helps audiences understand the impact of environments on personal outcomes. In media advocacy, the goal is often to reframe from episodic to thematic frames, which we liken to the difference between stories framed as portraits focused narrowly on individuals or events and those framed as landscapes that can reveal the context surrounding individuals and events (13).…”
Section: Theoretical Underpinnings Of Media Advocacymentioning
confidence: 99%
“…Iyengar (18) has found that such episodic news results in audience interpretations that tend to blame the victim, whereas more thematic news helps audiences understand the impact of environments on personal outcomes. In media advocacy, the goal is often to reframe from episodic to thematic frames, which we liken to the difference between stories framed as portraits focused narrowly on individuals or events and those framed as landscapes that can reveal the context surrounding individuals and events (13).…”
Section: Theoretical Underpinnings Of Media Advocacymentioning
confidence: 99%
“…27,28 This discursive agreement is required for researchers to generate evidence-based recommendations that are salient to, and executable within, a decision maker's range of action and priorities. A further step is to include government and health system officials directly in the research process either by means (deemed "linkage and exchange" or what some have called "integrated KT").…”
Section: Kt For Policy: Taking Power and Politics Seriouslymentioning
confidence: 99%
“…Decision makers remain the primary targets of every advocacy plan. Civil Society Organizations generally make up the secondary targets while the public constitutes the tertiary targets [11]. In Cameroon, newspapers and magazines are used and consumed mostly by those who make policy (primary targets) and those who pressure for advancements in policy (secondary targets).…”
Section: Media Advocacy Vs Reportingmentioning
confidence: 99%